Risk Factors of Respiratory Diseases Among Neonates in Neonatal Intensive Care Unit of Qena University Hospital, Egypt - Khaled A. Abdel Baseer; Mostafa Mohamed; Eman A. Abd-Elmawgood (Ubiquity Press, 2020)
Background: Respiratory diseases in newborns are considered major causes of neonatal morbidity and mortality especially in developing countries. Its causes are diverse and require early detection and management. This study aimed for detection of the prevalence and risk factors of respiratory diseases in addition to outcome among neonates admitted in neonatal intensive care unit. Methods: Our study was a prospective observational study that was undertaken at the neonatal intensive care unit of Qena University Hospital, Egypt from July 2017 to July 2018. Demographic and clinical data of newborns and their mothers were evaluated and tabulated. Results: In this period, 312 neonates were admitted to the neonatal intensive care unit, out of them 145 suffered respiratory diseases giving a prevalence of (46.5%), and (55.9%) were males. The mean neonatal age at admission was 4.33 ± 7.19 days and mean gestational age was 34.49 ± 3.31 weeks. The most common detected respiratory diseases were respiratory distress syndrome (RDS; 49.6%), transient tachypnea of newborn (TTN; 22%), neonatal pneumonia (17.2%) and meconium aspiration syndrome (MAS; 6.21%). Premature rupture of membrane (PROM), maternal diabetes and fetal prematurity had the highest risk factors for respiratory diseases occurrence in neonates. Neonatal mortality rate was 26.2%, mainly due to hyaline membrane disease and pneumonia. Conclusion: Respiratory diseases constitute major part of total admission in neonatal intensive care unit especially RDS, TTN, pneumonia and MAS. Prematurity and maternal diabetes were the most important risk factors associated with respiratory diseases. Respiratory distress syndrome carried the highest risk of mortality and TTN carried the highest survival rate.